Efficacy of an inactivated bivalent vaccine for enterovirus 71 and coxsackievirus A16 in mice immunized intradermally. Issue 3 (15th January 2021) - Fan, Shengtao; Liao, Yun; Jiang, Guorun; Wang, Lichun; Zhao, Heng; Yu, Li; Xu, Xingli; Li, Dandan; Zhang, Ying; Li, Qihan
Highlights: Intradermal immunization reduces the inflammatory reaction. Intradermal immunization induces a robust immune response in mice. EV71- and CA16-induced immunity is related to time specificity. Bivalent EV71-CA16 inactivated vaccine was effective in mice. Abstract: Human hand, foot, and mouth disease (HFMD), an important infectious disease in children, is caused mainly by enterovirus 71 (EV71) and coxsackievirus A16 (CA16). In this study, a bivalent inactivated EV71/CA16 vaccine is developed and evaluated in immunized BALB/c mice injected through the intradermal route. Q-RT-PCR detection of the mRNA of immune signal molecules in local epithelial tissues inoculated with the vaccine indicates activation of innate immunity, which includes upregulation of immune-related chemokines, interferons and CD molecules. Further, the finding that neutralizing antibodies and specific T cellular responses were elicited in adult mice after two immunizations with the vaccine at a 28-day interval, which endowed offspring mice to defend a viral challenge, suggests the successful induction of specific protective antiviral immunity. All these data suggest that immunization with this bivalent EV71/CA16 vaccine via the intradermal route elicits effective immunity against EV71 and CA16 infection.